PEMANFAATAN LAYANAN AMERICAN CORNER DI UPT PERPUSTAKAAN INSTITUT TEKNOLOGI BANDUNG (ITB) - Siraj Fauzan, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
The purpose of this research is to know the Utilization of American Corner Services at Upt Library of Bandung Institute of Technology (ITB). This research method is descriptive qualitative research using data collection techniques through observation, interviews, and literature studies. Qualitative research is used to truly describe / explain an event or event and capture the meaning that exists in the area under study. The advantage of qualitative research is that data or information can be traced and obtained as comprehensively as possible after a good and correct variation discusses the benefits of existing services in the library and has the aim of knowing the utilization of information and programmed activities of the American Corner service by its users. The research method used is qualitative descriptive with data collection techniques through observation, interviews, and literature studies. The result of this research is that we can find out from the utilization of information and programmed activities from the American Corner service. As well as the obstacles faced by users in searching for information at the American Corner.